2008
DOI: 10.2340/16501977-0160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of home modification services on ability in everyday life for people ageing with disabilities

Abstract: Home modifications have a positive impact on self-rated ability in everyday life, especially on decreasing the level of difficulty and increasing safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 25 publications
(30 reference statements)
4
93
0
5
Order By: Relevance
“…Based on the scientific evidence available [21,23,51], also functioning in terms of ADL capacity would be positively affected [17]. Since older people often want to live at home as long as possible [52], this is of importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the scientific evidence available [21,23,51], also functioning in terms of ADL capacity would be positively affected [17]. Since older people often want to live at home as long as possible [52], this is of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapists make recommendations for housing adaptions based on assessment of the transactions between individuals, the characteristics of the physical environment and their daily occupations based on individual needs [15]. Studies in Sweden have demonstrated that housing adaptations increases accessibility [16], improves self-related ability in everyday life [17] as well as the usability of the home [18]. Further, housing adaptations reduces the number of falls [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that HA improves the usability of the home [10,11] increases independence in daily activities [11,12,13] and reduces the number of falls [13,14]. However, no studies on long-term outcomes of HA have been presented.…”
Section: Introductionmentioning
confidence: 94%
“…The questionnaire was constructed based on previous research on housing adaptations (1,7,(12)(13), current Swedish housing adaptation legislation, and national guidelines (4,18).…”
Section: Survey Questionnairementioning
confidence: 99%
“…In a systematic overview of studies targeting outcomes of housing adaptations (6), substantial evidence of reduced disability, for example dependence in ADL and IADL, was found in some studies, (3,5,(7)(8)(9)(10)(11)(12) but other studies (13)(14)(15) indicated that the intervention had no such effects. Instead, multidimensional interventions comprising a variety of strategies, e.g.…”
Section: Introductionmentioning
confidence: 99%